Altered Caecal Neuroimmune Interactions in the Neuroligin-3R451C Mouse Model of Autism - Sharna, Samiha Sayed; Balasuriya, Gayathri K.; Hosie, Suzanne; Nithianantharajah, Jess; Franks, Ashley E.; Hill-Yardin, Elisa L. (Frontiers in Cellular Neuroscience, 2020)
The intrinsic nervous system of the gut interacts with the gut-associated lymphoid tissue (GALT) via bidirectional neuroimmune interactions. The caecum is an understudied region of the gastrointestinal (GI) tract that houses a large supply of microbes and is involved in generating immune responses. The caecal patch is a lymphoid aggregate located within the caecum that regulates microbial content and immune responses. People with Autism Spectrum Disorder (ASD; autism) experience serious GI dysfunction, including inflammatory disorders, more frequently than the general population. Autism is a highly prevalent neurodevelopmental disorder defined by the presence of repetitive behaviour or restricted interests, language impairment, and social deficits. Mutations in genes encoding synaptic adhesion proteins such as the R451C missense mutation in neuroligin-3 (NL3) are associated with autism and impair synaptic transmission. We previously reported that NL3R451C mice, a well-established model of autism, have altered enteric neurons and GI dysfunction; however, whether the autism-associated R451C mutation alters the caecal enteric nervous system and immune function is unknown. We assessed for gross anatomical changes in the caecum and quantified the proportions of caecal submucosal and myenteric neurons in wild-type and NL3R451C mice using immunofluorescence. In the caecal patch, we assessed total cellular density as well as the density and morphology of Iba-1 labelled macrophages to identify whether the R451C mutation affects neuro-immune interactions. NL3R451C mice have significantly reduced caecal weight compared to wild-type mice, irrespective of background strain. Caecal weight is also reduced in mice lacking Neuroligin-3. NL3R451C caecal ganglia contain more neurons overall and increased numbers of Nitric Oxide (NO) producing neurons (labelled by Nitric Oxide Synthase; NOS) per ganglion in both the submucosal and myenteric plexus. Overall caecal patch cell density was unchanged however NL3R451C mice have an increased density of Iba-1 labelled enteric macrophages. Macrophages in NL3R451C were smaller and more spherical in morphology. Here, we identify changes in both the nervous system and immune system caused by an autism-associated mutation in Nlgn3 encoding the postsynaptic cell adhesion protein, Neuroligin-3. These findings provide further insights into the potential modulation of neural and immune pathways.